Damage of Teak Trees (Tectona grandis Linnaeus filius) in the Production Forest Area of RPH Sukorame, KPH Mojokerto, East Java, Indonesia - Ida Ayu Ashari; Erni Mukti Rahayu; Joko Triwanto (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2022)
The health of the teak tree can be affected by damage caused by pests and environmental factors. This study aims to determine the health of the teak tree in teak production forest areas at RPH Sukorame KPH Mojokerto, East Java, Indonesia. The method used was the forest health monitoring (FHM) method. The sample was chosen by using a cluster plot system with a total sample of 216 teak trees. Parameters observed were symptoms of damage and its causes, type of damage and damaged parts of the teak tree, height and diameter, tread quality, and tree health analysis. The results showed that the health level of the teak tree in the teak production forest area of RPH Sukorame, KPH Mojokerto, East Java, was included in the health category with a Cluster plot level index (CLI) value of 4.36 - 4.51. The damage to the stand was caused by the attack of armyworm (Hyblaea puera), termites (Schedorhinotermes sp), and other factors. The productivity level of the area could have been more optimal, with a branch-free stand height of 0-5 m and a diameter of 16-20 cm: grumusol and grumusol sandy soil with a pH ranging from 5.8 to 7.0. Forest management is needed so that the teak tree can achieve optimum productivity.